SYSTEM OF PRACTICAL LESSONS 3 COURSES "MONEY AND CREDIT" IN HIGHER EDUCATIONAL INSTITUTIONS ECONOMIC DIRECTION (Pedagogy of Higher and Secondary Education, 2008)
This article examines the features of teaching of the course “Money and credit” in conditions of modern economic education in high educational institutions. It accents attention on the students' skills to use their knowledge in practical activity, to decide non-standard situations and tasks, to be able to interact in groups.The formation of these abilities is realized by means of use at the practical studies both traditional and active “interactive ” methods of the teaching. The system of the practical studies to the course “Money and credit” was worked out in this article.